Pengaruh Opinion Shopping, Financial Distress dan Share Growth terhadap Pergantian Kantor Akuntan Publik (KAP)(Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia BEI Periode 2012-2014) - Alkatiri, Amrah, Dr.Noer Sasongko,SE, Msi (2016)
This study aimed to examine the effect of the change of KAP Opinion Shopping. To test the effect of Financial Distress affect the turn of KAP. To test the effect on turnover Share Growth KAP. The population in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) during 2012-2014. And sample in this research manufacturing companies listed in Indonesia Stock Exchange during the period 2012-2014. Based on these results Opinion shopping variables affect the turn of KAP. Variable financial distress does not affect the change of KAP. Variable share growth did not affect the change of KAP.